Pengembangan Media Magic Box Pada Pembelajaran IPA Di SD Negeri 105359 Sumberjo - Ayu Dewi Sartika, Samsul Bahri (Ability: Journal of Education and Social Analysis, 2022)
The objective of this research was to develop a science learning media that can overcome the problem in SD grade IV in the material of grouping animals based on the type of food, where they live, and how to breed. The methods used in this research were research and development (R&D) methods. Product development in this research used the ADDIE (Analysis, Design, Development, Implement, and Evaluation) model, but this research was only carried out up to the development stage. This research was conducted at SD Negeri 105359 Sumberjo. The data collection instrument used was questionnaire. The subjects in this research were 3 validators, namely media expert lecturers and material experts who come from lecturers of Universitas Muslim Nusantara AW Medan and grade IV teachers. Based on the analysis of research results and discussions, it could be concluded that on the validation of material and media experts and teacher responses were carried out in two stages with one revision. That way the media is declared good and worth using with revisions.